If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7u + 4 = 4 + -7u Reorder the terms: 4 + 7u = 4 + -7u Add '-4' to each side of the equation. 4 + -4 + 7u = 4 + -4 + -7u Combine like terms: 4 + -4 = 0 0 + 7u = 4 + -4 + -7u 7u = 4 + -4 + -7u Combine like terms: 4 + -4 = 0 7u = 0 + -7u 7u = -7u Solving 7u = -7u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '7u' to each side of the equation. 7u + 7u = -7u + 7u Combine like terms: 7u + 7u = 14u 14u = -7u + 7u Combine like terms: -7u + 7u = 0 14u = 0 Divide each side by '14'. u = 0 Simplifying u = 0
| 8-7n=34 | | 2k^2-7k=0 | | 5xm=d | | 7n+8=34 | | 0(t)=3.25t^2+-75 | | 6x-(3y)=15 | | 34-8=7n | | s(t)=3.25t^2-75 | | 4x^3-12x+8= | | 4w+4=6w+14 | | 5(7p-5)-[2(2p-3)+4]= | | 60-3(9-5)3= | | In(x)+In(x-2)=In(3) | | 5-9-7-1= | | 3x(-2x-7)-2y=9 | | 12-2y=8y+4 | | -6(2y-1)=3.6 | | 25.0139-7.481x=-1.1(x-8) | | 4x=15-5y | | -9p+21+16p=5(p+4)+3 | | 2x-11=38+9x | | -2m-6+8m=-4m-2+10m | | 6.5(1+0.495*1.2)=5.114+4.3*1.2 | | 3p+3(p+2)=6p+2 | | 6.5(1+0.945*1.2)=5.114+4.3*1.2 | | -2z-9=-2z-10+1 | | 6t-9=3(2t-4)+3 | | 4x+2(4+x)=3(2+5x) | | 618.5172=2*3.14*24.01+2*3.14*4.9*h | | 3.6x-1.2=.7(10-x) | | 6.5(1+0.495x)=5.114+4.3x | | 19694.08=2*3.14*196+2*3.14*14*h |